Asymmetric Disulfonimide‐Catalyzed Synthesis of δ‐Amino‐β‐Ketoester Derivatives by Vinylogous Mukaiyama–Mannich Reactions1. Issue 49 (27th October 2014) - Wang, Qinggang; van Gemmeren, Manuel; List, Benjamin
Abstract An organocatalytic asymmetric synthesis of δ‐amino‐β‐ketoester derivatives has been developed. A chiral disulfonimide (DSI) serves as a highly efficient precatalyst for a vinylogous Mukaiyama–Mannich reaction of readily available dioxinone‐derived silyloxydienes with N‐Boc‐protected imines, delivering products in excellent yields and enantioselectivities. The synthetic utility of this reaction is illustrated in various transformations, including a new CC bond‐forming reaction, which provide useful enantioenriched building blocks. The methodology is applied in a formal synthesis of (−)‐lasubin.